Eight Years of Labor Reform: Trade Unions and Collective Bargaining (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article reflects on the impacts of Law No. 13,467/2017 on the Brazilian trade union structure and the dynamics of collective bargaining. The author examines the transition from a rigid legal protection model to the collective autonomy encouraged by the "negotiated over legislated" principle. It discusses the end of mandatory union dues, the weakening of class entities, and the need for trade union self-reform to face the new challenges of the world of work, especially in light of the jurisprudence established by the STF in Theme 1,046. (Received: June 2025 | Accepted: September 2025).
Keywords: Trade Unions; Collective Bargaining; Labor Reform; Collective Autonomy